RACISM ISSUES IN NIKE BRAND ADVERTISEMENT - Rafi, Muhammad Abyan; Jasjfi, Elda Franzia (Universitas Ciputra, 2020)
Racialism is a social issue that has become a culture in major countries. Many protest movements against social issues, starting from the community, an organization, to a well-known brand, one of which is Nike. Nike is one of the most well-known and successful sports brands in terms of products and athletes in all sports. This is one of the keys to the success of the Nike brand in awakening the world to the issue of racism, which is widely shown through its visual campaign in the form of an official Nike poster advertisement entitled “Believe in something. Even if it means sacrificing everything